2015
DOI: 10.1111/bju.13160
|View full text |Cite
|
Sign up to set email alerts
|

Bone Scan Index predicts outcome in patients with metastatic hormone‐sensitive prostate cancer

Abstract: ObjectiveTo evaluate the Bone Scan Index (BSI) for prediction of castration resistance and prostate cancer-specific survival (PCSS). In this retrospective study, we used novel computerassisted software for automated detection/quantification of bone metastases by BSI. Patients with prostate cancer are M-staged by whole-body bone scintigraphy (WBS) and categorised as M0 or M1. Within the M1 group, there is a wide range of clinical outcomes. The BSI was introduced a decade ago providing quantification of bone met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…The automated BSI for the assessment of skeletal tumor burden in patients with prostate cancer is an example of such a diagnostic tool. The BSI has been proven to be valuable for prognostication, prediction, and response assessment in prostate cancer patients (11,(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…The automated BSI for the assessment of skeletal tumor burden in patients with prostate cancer is an example of such a diagnostic tool. The BSI has been proven to be valuable for prognostication, prediction, and response assessment in prostate cancer patients (11,(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have demonstrated the usefulness of BSI, unfortunately, only a few have included significant clinical information such as blood data. Poulsen et al [8] iPSA, initial prostate-specific antigen; Hb, hemoglobin; LDH, lactate dehydrogenase; CRP, C-reactive protein; EOD, extent of disease on bone scan; ALP, alkaline phosphatase; BSI, bone scan index.…”
Section: Discussionmentioning
confidence: 99%
“…Bone scan index (BSI, i.e. total skeletal uptake on 99m Tc-diphosphonate bone scanning) has been shown to be a useful predictor of outcome of time to castration-resistant prostate cancer and survival in patients with hormone-sensitive metastatic prostate cancer [19]. The TLF index investigated in this study is similar to BSI, but direct comparisons are needed before 18F-fluoride could be favoured.…”
Section: Discussionmentioning
confidence: 99%